União pontual por fricção (“friction spot joining”) de alumínio 6181-T4 com compósito laminado de poli(sulfeto de fenileno) e fibra de carbono (CF-PPS) - Esteves, João Victor Almeida (2015)
The friction spot joining (FSpJ) emerges as an alternative and innovative technique for producing polymer-metal hybrid structures. This technique was developed and patented by HZG / Germany in 2012. The process uses a combination of tools that by friction generates heat leading to the formation of a polymer layer through the interface and mechanical interlocking between the joints partners. Previous studies have demonstrated the technical feasibility of producing hybrid joints by FSpJ, however, no studies have demonstrated the influence of the process parameters on the joints properties. This study aimed to produce hybrid joints of 6181-T4 aluminum alloy and carbon fiber reinforced poly(phenylene sulfide) laminate composite (CF-PPS) by FSpJ and investigate the influence of process and aluminum surface treatment on the structure and the mechanical strength of these joints. The proper combination of these parameters resulted in hybrid joints with single lap shear force of up to 1861 N (29 MPa) and 3522 N (55 MPa) for double lap joints. This level of shear strength is similar or superior to others metal / polymeric composite joints produced by conventional joining techniques, demonstrating the potential of the FSpJ. The rotational speed (RS) was the parameter with the greatest influence on the shear strength of the joints, followed by the joining time (JT), tool plunge depth (PD) and joining force (JF). Joints that had predominantly cohesive fracture showed higher shear strength. Joints that were cooled at lower rates showed higher joint shear strength, regardless the heat input, due to lower residual stress at the interface of these joints. Through simple aluminum surface treatment (griding followed by acid pickling) it was possible to achieve an increasing up to 160% in the shear strength of the joints.